Determinants of Adolescent Pregnancy in Urban Slum Areas in Nigeria - Ajayi Edward (Syntax Corporation Indonesia, 2023)
Abstract The study investigated Determinants of Adolescent Pregnancy in Urban Slum Areas in Nigeria. The objectives of this study were to investigate whether; Family background, friends and peer pressure, lack of knowledge on human sexuality, sexual abuse and media influence are determinant of adolescent pregnancy in urban slum areas in Nigeria. Ex-post factor research and cross sectional survey method was used for the study. Population for this study comprised all adolescent girls in urban slum area, Nigeria. Multi-stage sampling techniques consisting of simple, purposive and proportionate sampling techniques were used to select 1305 respondents from 6 selected states in the six geopolitical zone. Data was collected with the use of researcher’s structured questionnaire and tested for reliability with the use of cronbach alpha. A reliability coefficient of r = 0.93 was obtained. The 5 formulated null hypotheses were tested using inferential statistics of one sample t-test at 0.05 alpha level of significance. The findings of this study showed that: Family background was a determinant of adolescent pregnancy in urban slum area, Nigeria because the calculated t- value t-3.693 is greater than t-cal. 1.960 at df (1285). Peer pressure was a determinant of adolescent pregnancy in urban slum area, Nigeria because the calculated t- value t-8.341 is greater than t-cal. 1.960 at df (1285). Lack of knowledge on human sexuality was a determinant of adolescent pregnancy in urban slum area, Nigeria because the calculated t- value t-2.847 is greater than t-cal. 1.960 at df (1286). Sexual abuse was a determinant of adolescent pregnancy in urban slum area, Nigeria because the calculated t- value t-7.091 is greater than t-cal. 1.960 at df (1285). Media influence was a determinant of adolescent pregnancy in urban slum area, Nigeria because the calculated t- value t-3.250 is greater than t-cal. 1.960 at df (1285). The study concluded that Family background, friends and peer pressure, lack of knowledge on human sexuality, sexual abuse and media influence are determinants of adolescent pregnancy in urban slum areas in Nigeria. The following recommendations were made: Parents must be encourage to attend workshops on sexuality education, make contributions towards developing the school policy on sexual education, and provide learners with adequate resource material. The empowerment of NGOs with grants, political supports and friendly policies that will enhance the effectiveness of their duties in ameliorating the menace of teenage pregnancy. Skills acquisition centers should be established in every LGA to help adolescents who cannot complete formal education to acquire skills that will make them independent.